Empirical factors affecting the work ethic of BRI employees, Jakarta III Auditor Office - Yumhi; Didit Haryadi; Paniran (Enrichment : Journal of Management, 2023)
This study explores the issues of competence, compensation, and job satisfaction on auditor work ethic in the BRI Jakarta III office, using a sample of 78 auditors. Data for each variable was collected separately by respondents who filled out questionnaires. The method used in this research is a quantitative survey, while the analysis technique is regression analysis. The results prove that there is an influence between competence on work ethic which shows that increasing competence will result in an increase in the work ethic of auditors. that an increase in job satisfaction will result in an increase in the work ethic of auditors. There is a joint influence of competence, compensation, and job satisfaction on work ethic indicating that increasing competence, compensation, and job satisfaction together will result in an increase in the work ethic of auditors. The uniqueness of this finding is that job satisfaction has a greater effect than competence and compensation, so organizations must pay attention to job satisfaction and the factors that cause it, so the BRI Jakarta III Auditor's office must increase job satisfaction until employees get optimal job satisfaction.